FEMINISME DALAM NOVEL GENI JORA KARYA ABIDAH EL KHALIEQY DAN IMPLIKASINYA DALAM PEMBELAJARAN SASTRA DI SEKOLAH - Taryanti Taryanti; Ahmad Bahtiar (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2015)
This paper describes feminism in the novel Geni Jora by Abidah El Khalieqy and its implications toward learning of literature in schools. The data which were analyzed in this paper are the novel Geni Jora by Abidah El Khalieqy and books that are related to the object of research, such as the study of feminism. The values of feminism contained in this novel include: female characters are 1) daring to disagree, 2) having aspirations and ambitions, 3) having a desired social status, 4) daring to compete, 5) able to attempt providing insight, 6) ending the relationship with strategy, 7) rejecting the restriction of education for women, 8) rejecting the restriction of freedom for women outside the home, 9) rejecting polygamy. Those values can be applied in the learning of Indonesian language and literature at the 11th grade of high school in the aspect of reading with the Standards of Competence of understanding various tales, Indonesian novels/translated novels and Basic Competence of analyzing the intrinsic and extrinsic elements of Indonesian or translated novels with learning indicators that students are able to find the intrinsic elements (plot, theme, characterization, perspective, background and mandate) and extrinsic elements (cultural values, social values, and the value of education) in Indonesian/translated novels. ai lebih dari satu bahasa. Tentunya mereka saat berpidato besar kemungkinan mencampuradukan bahasa yang mereka kuasai. Padahal, seharusnya siswa wajib menggunakan bahasa Indonesia yang baik dan benar ketika sedang berpidato. Dengan demikian pengenalan campur kode dalam berpidato ini sangat diperlukan dalam materi berpidato maupun dalam pembelajaran bahasa Indonesia.   ducted using a quantitative approach. This research uses the descriptive method. The population in this research is the whole Islamic Banking Majors semester IV amounted to 125. This research sample taken using proportional random sampling. Based on the model of random sample research, determined that Islamic Banking Majors semester IV class B and D of 59 people.  The results showed that in general a student majoring in Islamic Banking Semester IV is quite skilled in the critical reading of a text. It is reflected in the statistical data indicating that the average value of the total of the skills of critical reading of a text on Islamic Banking majors semester IV is at number 77,35 and is skilled enough to qualify. Specifically, the percentage of the skill level of every aspect of critical reading on Islamic Banking Majors Semester IV can be outlined as follows, (1) aspects of skills to determine the facts in the text represents 22.5% of the total critical reading skills, (2) aspects of skills to determine the opinion in the text represents 22.2% of the total critical reading skills, (3) aspects of skills conclude text content representing 20.3% of the total critical reading skills, (4) aspects of skills analyze the use of the language within the text represent 15.7% of the total critical reading skills, (5) aspects of skills opined against text content represent 19,3% of the total critical reading skills.